Carotenoid responds to excess energy dissipation in the LH2 complex from Rhodoblastus acidophilus - Šímová, Ivana; Kuznetsova, Valentyna; Gardiner, Alastair T; Šebelík, Václav; Koblížek, Michal; Fuciman, Marcel; Polívka, Tomáš (Photosynthesis research, 2022)
The functions of both (bacterio) chlorophylls and carotenoids in light-harvesting complexes have been extensively studied during the past decade, yet, the involvement of BChl a high-energy Soret band in the cascade of light-harvesting processes still remains a relatively unexplored topic. Here, we present transient absorption data recorded after excitation of the Soret band in the LH2 complex from Rhodoblastus acidophilus. Comparison of obtained data to those recorded after excitation of rhodopin glucoside and B800 BChl a suggests that no Soret-to-Car energy transfer pathway is active in LH2 complex. Furthermore, a spectrally rich pattern observed in the spectral region of rhodopin glucoside ground state bleaching (420-550 nm) has been assigned to an electrochromic shift. The results of global fitting analysis demonstrate two more features. A 6 ps component obtained exclusively after excitation of the Soret band has been assigned to the response of rhodopin glucoside to excess energy dissipation in LH2. Another time component, ~ 450 ps, appearing independently of the excitation wavelength was assigned to BChl a-to-Car triplet-triplet transfer. Presented data demonstrate several new features of LH2 complex and its behavior following the excitation of the Soret band.
Keywords: Beijerinckiaceae; Energy transfer; Glucosides; Light-Harvesting Protein Complexes; světlosběrné proteinové komplexy; Antenna complex; Carotenoids; Electrochromic shift; Bacteriochlorophylls; bakteriochlorofyly; Excess energy; glukosidy; karotenoidy; LH2